Pemanfaatan Limbah Kulit Buah Sebagai Ecoenzyme Untuk Pengolahan Palm Oil Mill Effluent - Netri Elisma; M Ikhlas Armin; Miftahurrahmah Miftahurrahmah; Apsari Puspita Aini; Melysa Putri (Fakultas Teknik Universitas Wahid Hasyim, 2025)
The palm oil industry plays a crucial role in the global economy, particularly in Indonesia as one of the leading producers of palm oil. However, its production process generates a substantial amount of liquid waste known as Palm Oil Mill Effluent (POME), which is rich in organic pollutants, including Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), as well as residual oil and grease. If not properly managed, POME can lead to environmental pollution and disrupt surrounding ecosystems. Conventional treatment methods, such as anaerobic ponds, induced air flotation, and coagulation–flocculation, present several limitations, including prolonged processing time and high operational costs. As an alternative, the use of eco-enzyme derived from the fermentation of organic waste, such as fruit peels, offers a more efficient and environmentally friendly solution. Eco-enzyme contains active enzymes, including lipase, protease, and amylase, which are effective in degrading complex organic compounds in POME, thereby naturally reducing BOD, COD, and TSS levels. Furthermore, the presence of organic acids and phenolic compounds in eco-enzyme contributes to pH neutralization and facilitates the adsorption of heavy metals in POME. This study aims to explore the potential of eco-enzyme as a sustainable technology for POME treatment, while also supporting the principles of zero waste and circular economy within the palm oil industry.